2017
DOI: 10.1111/jfpp.13207
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of heat treatment on alcalase-assisted hydrolysis of wheat gluten proteins: Functional and antioxidant properties

Abstract: In order to confirm the gluten potential for inclusion into functional foods, the synergistic effect of the heat treatment and controlled enzymatic hydrolysis on the functional and the antioxidant properties of alcalase‐assisted wheat gluten hydrolysates (AWGHs) will be discussed. For this purpose, wheat gluten was heat‐treated during 30 min at 75 °C and intensively hydrolyzed with alcalase at degree of hydrolysis (DH) 16.1%, 22.9%, and 30.2%. All the hydrolysates had excellent solubility over a pH range of 2–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…This could be due to the manufacturing process of bone extract, whereby the bones are pressure cooked in water for at least 2 h at 121 °C. Similar hydrolysis due to heat treatment had been reported for wheat gluten proteins (Elmalimadi et al ., ). Bone extract hydrolysed by Flavourzyme ® showed the highest DH compared to Protamex ® and bromelain at E/S ratio of 0.5–4% w/w.…”
Section: Resultsmentioning
confidence: 97%
“…This could be due to the manufacturing process of bone extract, whereby the bones are pressure cooked in water for at least 2 h at 121 °C. Similar hydrolysis due to heat treatment had been reported for wheat gluten proteins (Elmalimadi et al ., ). Bone extract hydrolysed by Flavourzyme ® showed the highest DH compared to Protamex ® and bromelain at E/S ratio of 0.5–4% w/w.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, foam stability was reduced in more extensive hydrolysis due to the increased polypeptide chains unable to make foam air cells stable Wouters et al, 2016;. Gluten treated with alcalase was further reported to increase solubility, emulsifying capacity, foaming stability, and foaming capacity owing to produce lower molecular size hydrolysates (Elmalimadi et al, 2017;He et al, 2019;Kong et al, 2007b). Deng et al, (2016) revealed that enzymatic hydrolysis is capable of breaking some SS bonds to unfold the globular structure of gluten and new SS bonds are generated between both newly generated SH and original free SH groups to stabilize the structure of smaller peptides.…”
Section: Effect On Functional Propertiesmentioning
confidence: 99%
“…On the other hand, foam stability was reduced in more extensive hydrolysis due to the increased polypeptide chains unable to make foam air cells stable (Wouters, Fierens, et al., 2017; Wouters et al., 2016; Wouters, Rombouts, et al., 2017). Gluten treated with alcalase was further reported to increase solubility, emulsifying capacity, foaming stability, and foaming capacity owing to produce lower molecular size hydrolysates (Elmalimadi et al., 2017; He et al., 2019; Kong et al., 2007b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the GSH/GSSG ratio is the major cellular redox buffer and the maintenance of GSH levels is an essential biological process [ 41 ]. Previous studies have shown the antioxidant properties of Alcalase 2.4 L-digested wheat gluten hydrolysates in cell-free in vitro systems [ 42 , 43 , 44 ]. Furthermore, in vitro treatment of the PC12 rat adrenal medulla cell line with WGPHs (0.25–1 mg/mL) protects against H 2 O 2 -induced oxidative stress [ 45 ].…”
Section: Discussionmentioning
confidence: 99%